Vicissitudes of International Trade Commitments by Colombia - Vilar Rubiano, Fabían Enrique (DIXI, 2015)
Purpose: Over the last decade, Colombia has concentrated its public policy for economic integration through intensive signature of international trade treaties that lead to the generation of rights and the acquisition of obligations, both internally and internationally. Threfore, the way in which the Colombian State fulfils the international trade obligations deriving from the Free Trade Agreements (fta) in force in Colombia becomes ever more important. Description: Ths article deals with the analysis of problems that can arise in the realm of incorporation of these ftas into the internal legal system. Point of view: Ths aspect could affct Colombia on the international stage and in relation to its trading policy in recent years, because of the process of honoring the principle of pacta sunt servanda in international law in the framework of the ftas. Conclusions: In this way, hermeneutics are used to examine the jurisprudence of the Constitutional Court when it has ruled certain aspects that are intimately related to the ftas as unconstitutional, making them true vicissitudes for the international trade commitments that Colombia must face.